1998
DOI: 10.1128/iai.66.10.4832-4837.1998
|View full text |Cite
|
Sign up to set email alerts
|

Urease Plays an Important Role in the Chemotactic Motility of Helicobacter pylori in a Viscous Environment

Abstract: Helicobacter pylori exhibits chemotactic responses to urea, flurofamide, acetohydroxamic acid, and sodium bicarbonate. In buffer, the chemotactic activities of a urease-positive strain were higher than those of the isogenic urease-negative strain. Moreover, the chemotactic activities of the urease-positive strain were increased in a viscous solution containing 3% polyvinylpyrrolidone, whereas those of the urease-negative mutant were not. These results are in accordance with the fact that the mutant strain did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Some chemicals that are continuously secreted from the gastric epithelial cells to the lumen such as urea, 72 sodium carbonate, 73 and potassium carbonate 74 serve as potent attractants for H. pylori toward higher pH. Despite these data, little is known about the chemotactic behavior of H. pylori at various pH levels of the stomach, ranging from highly acidic to pH 4.5-6.5, which is the ecological niche of this bacterium.…”
Section: Chemotactic Activitymentioning
confidence: 99%
“…Some chemicals that are continuously secreted from the gastric epithelial cells to the lumen such as urea, 72 sodium carbonate, 73 and potassium carbonate 74 serve as potent attractants for H. pylori toward higher pH. Despite these data, little is known about the chemotactic behavior of H. pylori at various pH levels of the stomach, ranging from highly acidic to pH 4.5-6.5, which is the ecological niche of this bacterium.…”
Section: Chemotactic Activitymentioning
confidence: 99%
“…At the onset as well as during the course of infection, H. pylori may encounter gastric acid that kills most of the bacteria. The microorganism produces urease to a concentration of up to 6% of soluble proteins (Hu and Mobley, 1990) and has the ability to move towards urea in a viscous environment (Nakamura et al, 1998). Urease (urea amidohydrolase; EC 3.5.1.5) catalyses the hydrolysis of urea to yield ammonia and carbamate, and the latter compound is spontaneously decomposed to yield another molecule of ammonia and carbonic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Urease is an important virulence factor in H. pylori and is essential for gastric colonization (Tsuda et al, 1994;Andrutis et al, 1995). It has been suggested that H. pylori senses gradients in urea which allow the bacteria to move towards the epithelial cells by chemotaxis; this offers an explanation for the decrease in adherence observed in our model for this mutant (Nakamura et al, 1998;Yoshiyama & Nakazawa, 2000). This may also explain the phenotype of mutant HM10, which was affected in an ORF homologous to the aspS gene, which is downstream of the cheV chemotaxis gene.…”
Section: Discussionmentioning
confidence: 60%